Analysis of Hydrogen Sulfide (H2S) and Hydrocarbon Composition of Natural Gas from GMS (Gas Metering Station) in PT. Pupuk Sriwidjaja Palembang - Rostyanesia, Rostyanesia; Salmahaminati, Salmahaminati; Vidya, Putri Dwinanda (Chemistry Department, Universitas Islam Indonesia, 2018)
Natural gas of GMS (Gas Metering Station) is an important component that must be analyzed routinely in PT. Fertilizer Sriwidjaja because it is the main material used in addition to Carbon dioxide (CO2) and water vapor in the manufacture of ammonia. The quality of natural gas will affect the ammonia and urea fertilizer product. The purpose of this research is to know the composition of hydrocarbons and to know the level of H2S gas in natural gas which is contained in GMS pipes. Determination of H2S levels was performed to find out the many catalysts used in the manufacture of ammonia gas.In determining the hydrocarbon composition, the first gas sample is taken using Stainless Steel Cylinder Tube. After the gas filled tube it was analyzed using GC (Gas Chromatography) and it will know the hydrocarbon composition of GMS. As for the determination of H2S level, the gas sample taken as much as 30 L through gas spreader and inserted into erlenmeyer with 10% Cd Acetate and NaOH. Subsequently, 1% PADAS (N, N-Dimethyl-p-phenylendiamine sulphate) and FeCl3 were added. After the solution changed to blue color then analyzed using UV-Vis Spectrophotometer in 660 nm wavelength.The results obtained are nitrogen-containing natural gas and various hydrocarbon components: methane, hexane, carbon dioxide, ethane, propane, i-butane, n-butane, i-pentane, and n-pentane with H2S 2,954 ppm with the largest composition of methane 85.89%. The results have been in accordance with the standards used in the Pusri Industry which apply the provision that the natural gas used should contain methane with concentrations greater than 70%